Perkembangan Teknologi Pembelajaran Hibrida di Era Pasca Pandemi - Muhamad Khoerudin; Dwi Noviani; Suwandi, Suwandi (CV. ULIL ALBAB CORP, 2024)
Hybrid learning has rapidly evolved in the post-pandemic era in response to the need for flexibility in education through the integration of online and face-to-face learning. This study employs a literature review and secondary data analysis to evaluate the challenges, such as the digital divide and educators' readiness, as well as the potential of hybrid learning to enhance education quality. The findings indicate that despite existing barriers, this model holds significant promise for creating a more inclusive and effective education system through appropriate policies, infrastructure support, and adequate teacher training.